A perspective on sepsis pathogenesis, biomarkers and diagnosis: A concise survey. Issue 4 (15th June 2020) - Kundu, Souvik; Tabassum, Shawana; Kumar, Ratnesh
Abstract: Sepsis is a potentially fatal physiological state caused by an imbalance in the body's immune response to an infection and is one of the most common causes for deaths in the non‐coronary intensive care unit worldwide. In this article, the state of art on sepsis is presented in a manner that facilitates easy comprehension also for the non‐medical researchers by introducing sepsis, its causes, extent and comparison of diagnostic techniques (conventional labeled as well as label‐free detection). The article also provides a comprehensive discussion on sepsis biomarkers, to help researchers from multi‐disciplinary domain in developing devices and ideas to complement the existing sepsis diagnosis systems for quick and premature detection of the physiological condition and reduce mortality by means of early treatments.